Analisis Akuntabilitas dan Transparansi Pengelolaan Dana Bos Pada Sekolah Ma Bahrul Ulum Muliasari - Arvi Syai’in Wawan; Andrian Noviardy (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to examine the implementation of accountability and transparency principles in the management of School Operational Assistance (BOS) funds at MA Bahrul Ulum Muliasari. A descriptive qualitative approach was employed based on the applicable technical guidelines for BOS fund management. The findings indicate that planning and utilization of funds have complied with official regulations and involved the internal school management team, including the principal, treasurer, teachers, and school committee. However, parents and the broader community were not actively involved in the decision-making process. In terms of accountability, fund usage was supported by proper administrative documentation and aligned with the School Activity and Budget Plan (RKAM). Nevertheless, transparency has not been fully optimized, as information regarding fund allocation and realization has not been consistently disseminated through accessible public media. Therefore, while regulatory compliance has been achieved, greater openness in financial information disclosure remains necessary.